If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6+5(-x)=2(-x)+4
We move all terms to the left:
-6+5(-x)-(2(-x)+4)=0
We add all the numbers together, and all the variables
5(-1x)-(2(-1x)+4)-6=0
We multiply parentheses
-5x-(2(-1x)+4)-6=0
We calculate terms in parentheses: -(2(-1x)+4), so:We get rid of parentheses
2(-1x)+4
We multiply parentheses
-2x+4
Back to the equation:
-(-2x+4)
-5x+2x-4-6=0
We add all the numbers together, and all the variables
-3x-10=0
We move all terms containing x to the left, all other terms to the right
-3x=10
x=10/-3
x=-3+1/3
| Y=0.13x+11 | | 5x-9=5(2x-1)+6 | | 7h=399 | | 15-2x=21-4x | | w/11=17 | | h/15-17=-1315h −17=−13 | | 80=17x-5 | | 7=z/9 | | u/5+37=47 | | 1/8(x+48)=-30 | | -1=-5/8x+9 | | -30=5(3x+4)-5 | | 6x-4=10x-13-x | | d/5-8=67 | | -30=3(3x+5) | | w+24/8=6 | | 1+2(m+)=29 | | 18p+6=16p+14 | | 9(x+12)=198 | | 8v+3=105 | | 85=7g+8 | | x+27=-18 | | r+35/7=8 | | (4b-3)^2+6(4b-3)-72=0 | | 6(p+94)=12 | | -18=-1-1.5m | | 34+p=52;18,19,20, | | p/3-(-24)=28 | | 8^(x)-1=3.4 | | -9-14k=10 | | 2k/3-5=1 | | 20025=z225200 =2z |